OPTIMIZING PRECISION BLOOD MANAGEMENT MODEL BASED ON BIG DATA - Huihuan Xu, (Chelonian Research Foundation, 2023)
This study aims to enhance blood management through the optimization of a precision model leveraging big data analytics. We explore the impact of various factors on blood-related parameters, focusing on efficiency, cost-effectiveness, and patient outcomes. The research incorporates advanced data analytics techniques to derive valuable insights for improving blood management practices. Keywords: Precision Blood Management, Big Data Analytics, Efficiency, Cost-effectiveness, Patient Outcomes